The impact of ESG ratings on the quality and quantity of green innovation of new energy enterprises - Liu, Haiwen; Xu, Yuanze (Frontiers in Energy Research, 2024)
Amidst growing environmental challenges linked to coal dependence, fostering green innovation in new energy enterprises is vital for sustainable development in China. Although there have been studies on green innovation of new energy enterprises in recent years, few studies have been conducted from the perspective of ESG, whether informal environmental regulation represented by ESG can stimulate the green innovation of new energy enterprises is of great significance to China’s construction of a low-carbon and secure energy system. In this paper, from the perspective of informal environmental regulation, based on the ESG ratings of SynTao Green Finance’s first public new energy listed companies as an exogenous shock, and taking A-share new energy listed companies as a sample from 2010 to 2021, we empirically verified the effect and mechanism of ESG ratings on the green innovation of new energy companies in terms of the quantity and quality of green innovations by utilizing the Staggered Difference-in-difference (DID) model. The findings demonstrate that new energy enterprises’ green patent numbers and quality are greatly enhanced by ESG grading. However, there is clear heterogeneity in this green innovation effect, which is particularly visible in new energy firms with state-owned enterprise and greater enterprise scales and a higher level of digitization. The Mechanistic findings suggest that ESG ratings drive green innovation by alleviating financial constraints, reducing agency risk, and boosting R&D, thus providing empirical evidence for the development of a green innovation ecosystem in the new energy industry.